2020
DOI: 10.4103/ija.ija_49_20
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intrathecal fentanyl on the incidence, severity, and duration of postdural puncture headache in parturients undergoing caesarean section: A randomised controlled trial

Abstract: Background and Aims: Postdural puncture headache (PDPH) is a side effect of spinal anaesthesia (SA). This study was conducted to investigate the effect of intrathecal fentanyl on the incidence, severity, and duration of PDPH. Methods: This was a prospective randomised controlled study including 220 parturients, who underwent Caesarean section (CS). They were divided into two groups for administration of SA with bupivacaine (bupivacaine group [B0], n = 111) or bupivacain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…The incidence of PDPH in our study was less in fentanyl group as compared to control group which was statistically insignificant (graph 1). Similar results has been reported previously where addition of opioids to local anesthetic have decreased the severity and duration of PDPH but has not reduced the incidence of PDPH [5,6] . The mechanism is not known but it has been suggested that it could be due to systemic absorption of intrathecal morphine.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The incidence of PDPH in our study was less in fentanyl group as compared to control group which was statistically insignificant (graph 1). Similar results has been reported previously where addition of opioids to local anesthetic have decreased the severity and duration of PDPH but has not reduced the incidence of PDPH [5,6] . The mechanism is not known but it has been suggested that it could be due to systemic absorption of intrathecal morphine.…”
Section: Discussionsupporting
confidence: 91%
“…Severity of headache and Visual Analogue Scale score for pain intensity of PDPH was mild in fentanyl group as compared to control group (Table 2). The severity of PDPH differs significantly in control group as compared to opioid group as indicated by higher VAS score [6,8,10,12] . The difference in the incidence of backache, nausea, vomiting, vertigo, pruritis was not statistically significant between the groups and no other symptom was observed in either group (graph 2).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Although intrathecal opioids are used daily worldwide in combination with local anesthetics, there is no clear study situation as to which opioid is ideal for caesarean delivery. In the last 25 years, five systematic reviews have dealt with this question in the broadest sense, as well as several randomized controlled trials [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. The first systematic review found that, in a relatively small total number of patients, intrathecal fentanyl and sufentanil have no advantage over the administration of local anesthetics alone.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, Ali et al . [ 12 ] and Prakash et al . [ 13 ] attempted to shed some light on PDPH through their studies in the present issue of IJA.…”
mentioning
confidence: 99%